2010
DOI: 10.1590/s0100-204x2010000700007
|View full text |Cite
|
Sign up to set email alerts
|

Parent selection for cocoa resistance to witches'-broom

Abstract: -The objective of this work was to identify genotypes with high general combining ability for resistance to witches'-broom (Moniliophthora perniciosa) in populations formed from a first cycle of recurrent selection. Highly productive and resistant clones from different origins were interbred using the North Carolina II design. The clones SCA 6, CSUL 7, RB 39, CEPEC 89, OC 67, BE 4, EEG 29 and ICS 98 were used as paternal parents, while the maternal ones were NA 33, CCN 10, IMC 67, P 4B, CCN 51, CEPEC 86, SGU 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 6 publications
2
9
0
4
Order By: Relevance
“…Thus, results obtained in this study confirmed those obtained by Silva et al (2010) and others authors, in which RB39, NA33, P4B, RB36 and CSUL3 are highly recommended for PMGC as parents for new crosses, aiming at the association of genes for resistance to WB, at the expanding genetic diversity, and at greater resistance durability. …”
Section: Cs Benjamin Et Alsupporting
confidence: 89%
“…Thus, results obtained in this study confirmed those obtained by Silva et al (2010) and others authors, in which RB39, NA33, P4B, RB36 and CSUL3 are highly recommended for PMGC as parents for new crosses, aiming at the association of genes for resistance to WB, at the expanding genetic diversity, and at greater resistance durability. …”
Section: Cs Benjamin Et Alsupporting
confidence: 89%
“…Progenies of 59 crosses (among progenies selected by the combinatorial ability of parents and 'per se' plant performance, on the basis of results achieved by Silva et al 2010) and three controls (two susceptible -Catongo and SIC 23 and one resistant -SCA 6) were evaluated, totaling 62 treatments. Significant effects were observed for trial and replication within trial, and then the means of progenies were compared based on the means adjusted for these effects (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A first cycle of selection was established with crosses arranged in the North Carolina II design (Comstock and Robinson 1952), between two groups of genotypes from the Cepec's Germplasm Collection previously selected for witches' broom and black pod disease resistance, productivity, fat content and hardness, and other traits of interest (Silva et al 2010). From these crosses 13 new parents were selected for a second recurrent selection cycle based on the combining ability of their parents and 'per se' plant performance.…”
Section: Study Site and Plant Materialsmentioning
confidence: 99%
“…relação aos demais clones testados, isso pode ser um indicativo de que, apesar dos seus genitores possuírem genes de resistência no seu genótipo, não conseguiram transmitir esses genes para sua descendência. Em um estudo que identificou genótipos com alta capacidade geral de combinação quanto à resistência à VB, ficou comprovado que, embora seja resistente, o clone CCN51, não possui alta capacidade geral de combinação (Silva et al, 2010 CP 79,84,149,421,300,302,306, 309 e 431, apresentaram menor incidência de vassoura, com mínimo de 0,89 % e máximo de 6,2 % de plântulas infectadas. Os padrões de resistência (SCA6) e de suscetibilidade (ICS1), não diferiram estatisticamente, sendo este um comportamento inesperado.…”
Section: Resultsunclassified
“…Nesse sentido, o Centro de Pesquisas do Cacau (Cepec) tem desenvolvido estratégias focadas no manejo integrado da doença, incluindo, principalmente, a melhoria do nível de resistência e durabilidade das novas variedades comerciais (Silva et al, 2010). A resistência durável, conceitualmente, é aquela que se mantém efetiva em dada variedade que é amplamente cultivada por longo tempo em ambiente favorável a doença (Johnson, 1983).…”
Section: Introductionunclassified